PERSPECTIVES TEACHING AND LEARNING IN PRE-SCHOOL EDUCATION - Asadullayeva Mastura Abduvahobovna, Asadullayeva Mastura Abduvahobovna (Журнал иностранных языков и лингвистики, 2021)
The main goal of environmental education is to develop in preschool children a conscious attitude to the environment and its problems, as well as the knowledge, skills and competencies to find optimal solutions to them. In this sense, the article analyzes the purpose of environmental education in preschool education.